Investigating diverse sources of variation in the amount of time Weddell seal ( Leptonychotes weddellii ) pups spend in the water during the lactation period - Shane M. Petch; Jay J. Rotella; William A. Link; J. Terrill Paterson; Robert A. Garrott (Marine Mammal Science, 2023)
Field observations suggest that time spent in the water by Weddell seal pups during lactation varies among individuals, which could yield important developmental tradeoffs. We analyzed data from 713 pups born to 419 different mothers over 9 years to evaluate total time in the water, age at first entry, and potential sources of variation using temperature loggers attached to the rear flipper of pups. Pups first entered the water at 11–29 days of age ( M = 14.9) and spent 4–204 hr ( M = 69.3) in the water by 30 days of age. Age at first entry was earlier for pups with higher birth mass and mothers of above average reproductive experience. Total time in the water was related to maternal identity and greater for female pups and for pups that had higher birth mass, mothers of intermediate age, mothers that skipped reproduction in the previous year, and for pups that first entered the water at younger ages. Phenotypic traits explain observed variation in the development of a key life history behavior in the Weddell seal. Strong individual variation in time spent in metabolically costly swimming and diving might lead to variation in growth, energy stores, and survival and fitness outcomes.